Novel alginate-chitosan amine-functionalized silica coated magnetic composite for heavy metals removal in water - Dagil, Gimba Joshua (Malaysian Analytical Sciences Society, 2023)
A new effective biopolymer alginate chitosan amine-functionalized silica coated magnetic composite (alg/Cs-NH2-SiO2/Fe3O4) adsorbent was synthesized and applied for the first time to remove Pb(II), Cu(II) and Cd(II) from aqueous solution by utilizing inductive coupled plasma-optical emission spectroscopy (ICP-OES). The properties of the composite were characterized using Fourier-transform infrared spectroscopy (FTIR), Field emission scanning electron microscopy/energy-dispersive X-ray spectroscopy (FESEM/EDX), and vibrating sample magnetometry (VSM). Evaluation of alg/Cs-NH2-SiO2/Fe3O4 adsorption performance at optimum conditions revealed that the adsorbent had a maximum adsorption capacity of 41.79, 39.21, and 39.56 mg/g for Pb(II), Cu(II) and Cd(II), respectively. The adsorbent behavior was studied using Langmuir, Freundlich, Temkin, and Dubinin-Rudushkevich’s isotherm models. The Langmuir isotherm and the pseudo-second-order were better fitted with the coefficient of determination (R2) value of 0.99, indicating homogeneous surface and chemisorption processes. The thermodynamic factors indicated endothermic and spontaneous processes at 60 ℃. Even after the 5th cycle adsorption-desorption experiments, the adsorbent still retained its adsorption ability above 70% metal ions removal, indicating that the adsorbent was reasonable for metal ions removal in water. Pb(II) was detected in a river near an industrial area (Taman Mewah, Kulai, Johor), which was eventually removed by the adsorbent at 86% efficiency.